Sulfonated Polyethersulfone Membranes for Brackish Water Desalination: Fabrication, Characterization, and Electrodialysis Performance Evaluation - Li Chen; Eva M. Deemer; XiuJun Li; W. Shane Walker (Applied Sciences)
The widespread application of electrodialysis is constrained by the high cost of ion exchange membranes, necessitating the development of affordable alternatives. This study focuses on the fabrication and performance evaluation of cation exchange membranes made from polyethersulfone (PES) and sulfonated polyethersulfone (sPES). Membranes were synthesized through phase inversion with varying solvent evaporation times, using N-Methyl-2-Pyrrolidone (NMP) as the solvent. The structural and functional modifications were confirmed using FTIR, XPS, and AFM techniques. Performance tests identified optimal electrodialysis results for PES membranes with a 3 h solvent evaporation time and for sPES membranes with a 1 h evaporation time. Under varying operational conditions, including applied voltage, flow rates, and feed solutions, sPES membranes demonstrated superior performance, underscoring their potential for cost-effective brackish water desalination applications.